Scaling Innovations Food Legume Production in the Mixed Farming Systems of North Shoa, Ethiopia - Kassa, Yehuala; Ali, Bereket; Managido, Demis; Mamo, Dejenie; Girma, Natnael; Kemal, Seid Ahmed; Bishaw, Zewdie (International Center for Agricultural Research in the Dry Areas, 2024)
The highlands of Ethiopia are dominated by a mixed farming system where cereals (wheat, barley, and tef) and food legumes are important crops for food, income generation and their straw used for animal feed. The productivity of cereals and food legumes is low due to biotic and abiotic stresses, access to quality seeds of framer preferred crop varieties, pesticides, and other inputs (Kassa et al. 2024). The new faba bean gall disease is threatening faba bean production in the highlands of Ethiopia causing over 60% yield losses (Bitew et al. 2022). Therefore, farmers are reducing areas of faba bean crop and growing more cereals leading to low crop diversity that can reduce soil fertility, incomes, diet diversity, and increase pest outbreaks. Recently an effective seed treatment fungicide (Noble 25%WP) has been identified and is ready for large scale use by farmers in disease prone areas. Moreover, faba bean growers are producing seeds of framer preferred varieties since the fungicide is very effective (Bereket et al. 2022).